Hepatitis-B surface antigen and cirrhosis in Iraq. Issue 2 (February 1976) - Boxall, E H; Flewett, T H; Paton, A; Rassam, S W
Abstract : Hepatitis-B surface antigen was found in 58% of 64 patients with cirrhosis in Iraq using counter immunoelectrophoresis (CIE), radioimmunoassay (RIA), and three commercial haemagglutination tests--Auscell (Abbott Laboratories), Hepatest (Wellcome Reagents Ltd.), and Hepanosticon (Organon Teknika). CIE detected about half as many positives as the other methods; RIA was the most sensitive. The number of positive reactions was much higher than in any previously reported series of patients with cirrhosis and seven times higher than in a normal hospital control population.